ANALISIS HUBUNGAN PENGETAHUAN DAN SIKAP DENGAN PERNIKAHAN DINI PADA IBU USIA < 25 TAHUN DI DESA BARU WILAYAH KERJA PUSKESMAS PANCUR BATU KABUPATEN DELI SERDANG TAHUN 2018 - Andayani Boang Manalu; Sori Muda Sarumpaet; Putri Ayu Yessy Ariecha (Fakultas Kebidanan Institut Kesehatan Medistra Lubuk Pakam, 2018)
Early marriage is marriage that is done by teenagers under 20 years old who are not ready to carry out marriage. The design of this study is an analytical survey with cross sectional approach that aims to analyze the relationship of knowledge and attitude with early marriage in Desa Baru at working area Public Health Center of Pancur Batu in 2018. The population of this study is all mothers who are married <25 years old and live in the Desa Baru at working area of Pancur Batu as much as 227 people, and 61 sample which taken with purposive sampling technique, and consecutive technique sampling. Data analysis was done by Chi - Square test and logistic regression test. The data were collected by using primary validated questionnaires, and secondary data. The result showed that the early marriage 70,5%, the proportion of mother with less knowledge 54,1%, supporting attitude 55,7%, mother with low education 60,7%, parent with low education 62,3%, low economics 68,9 %, pregnant before marriage 6.6%, tribe / culture of Java 62.3%. There was a significant correlation between knowledge (p = 0,017, RP = 1,584), attitude (p = 0,010, RP = 1,645), mother’s education (p = 0,002, RP = 1,887), parent’s education (p = 0,006; RP = 1,761), economic (p = 0,003; RP = 1,979) with early marriage. Mother’s education is the most powerful variable relationship (OR = 4,137). It is recommended for mothers to continue higher education, increasing knowledge about maturation of marriage age by following Councelling & Information Center For Adolescent program and Construction Of Adolescent Family program, active role of Public Health Center and midwife who have on duty at village in increasing family knowledge about adolescent reproduction health especially the risk of early marriage.